A Systematic Review of Rhubarb (a Traditional Chinese Medicine) Used for the Treatment of Experimental Sepsis. (3rd August 2015) - Lai, Fang; Zhang, Yan; Xie, Dong-ping; Mai, Shu-tao; Weng, Yan-na; Du, Jiong-dong; Wu, Guang-ping; Zheng, Jing-xia; Han, Yun
Abstract : Sepsis is a global major health problem in great need for more effective therapy. For thousands of years, Rhubarb had been used for various diseases including severe infection. Pharmacological studies and trials reported that Rhubarb may be effective in treating sepsis, but the efficacy and the quality of evidence remain unclear since there is no systematic review on Rhubarb for sepsis. The present study is the first systematic review of Rhubarb used for the treatment of experimental sepsis in both English and Chinese literatures by identifying 27 studies from 7 databases. It showed that Rhubarb might be effective in reducing injuries in gastrointestinal tract, lung, and liver induced by sepsis, and its potential mechanisms might include reducing oxidative stress and inflammation, ameliorating microcirculatory disturbance, and maintaining immune balance. Yet the positive findings should be interpreted with caution due to poor methodological quality. In a word, Rhubarb might be a promising candidate that is worth further clinical and experimental trials for sepsis therapy.